Hybrid ventures - Corbett, Andrew C.; Katz, Jerome A. (Emerald Publishing Limited, 2017)
Contains an Open Access chapter. Recent estimates suggest that millions of people across the world are involved in some form of social venture creation. After over a decade of thoughtful scholarship on social entrepreneurship, researchers have now begun to examine individuals and organizations that purposefully combine social and economic outcomes. In Hybrid Ventures, leading researchers examine individuals and organizations that simultaneously attempt to pursue such bended value outcomes. Various perspectives on hybrid ventures are explored in this volume, including: the costs to all when some entrepreneurs do not pursue hybrid approaches, whether hybrid ventures are - or should be - the new norm, and whether the social, environmental, and economic value are distinct and should be separated from each other. This volume contains both theoretical and empirical approaches to hybrid venturing from an international group of researchers. Specific topics include: the emergence of Certified B Corporations, different hybrid business models, the role of impact investing, indigenous entrepreneurship, hybrid ventures as "agents of change," and more. For nearly two decades, the Advances in Entrepreneurship, Firm Emergence and Growth series has provided an annual examination of the major current research, efforts in the field of entrepreneurship and Hybrid Ventures: Perspectives & Approaches to Blended Value Entrepreneurship continue in that tradition. This volume provides state-of-the-art research that helps set the foundation for inquiries into important research for the next decade and beyond.- Resumé vydavatel
Obsahuje index.
Keywords: podnikání -- sociální aspekty; podnikatelé; business -- social aspects; businessmen; kolektivní monografie; elektronické knihy; collective monographs; electronic books